An evaluation study of the adequacy of lesson planning among art education teachers at the secondary level (Journal of the College of Basic Education, 2022)
The study aimed to evaluate the performance of art education teachers in the secondary stage in light of the school planning competencies. The study was conducted on a sample consisting of (70) teachers and a school of art education in Diyala governorate. The research tool consisted of a questionnaire consisting of (24) items for which the validity and reliability were extracted using statistical means, including the Pearson correlation, weighted mean and percentage weight. The researcher made a number of recommendations, including: 1- Holding training courses for art education teachers in order to develop their competence in general and the adequacy of school planning in particular. 2- Paying attention to art education teachers and urging them to keep pace with recent developments in the field of art education curricula and methods of teaching them. 3- Activating the role of educational supervision over teachers, such as holding a course of educational training workshops in the fields of preparing study plans that are consistent with educational standards.